Coping Strategies in Major Depression and Over the Course of Cognitive Therapy for Depression - Drapeau, Martin; Blake, Emily; Dobson, Keith S.; Körner, Annett (Canadian Journal of Counselling and Psychotherapy, 2017)
Background: Cognitive therapy (CT) aims to help patients recover from depression by teaching them to restructure their distorted thinking and to resolve practical problems in their lives. While studies have examined the role of cognitive variables in the treatment of depression, less research has focused on coping. Objectives: This study aimed to investigate the role of coping in depression, and changes in coping over the course of CT. Methods: Early and late therapy sessions were selected for 45 participants who received CT. Depression was assessed using the Beck Depression Inventory, and coping was assessed using the Coping Patterns Rating Scale. Results: Results indicated that information seeking, problem solving, and helplessness were the most prevalent coping strategies early in therapy; threat-based coping was correlated with depression; accommodation increased with therapy; and change in threat coping was correlated with change in depression. Conclusions: Findings indicate the importance of threat-based coping and of accommodation and delegation in depression and recovery from depression. Research and clinical implications are discussed.